THE CORRELATION OF UCS, UTS, PLI, AND YOUNG'S MODULUS OF INTACT ROCK IN ASEM-ASEM BASIN, SOUTH KALIMANTAN - Suhendar, Inzagi
This study aims to express the correlation between UCS and E, PLI and UCS, and UTS and UCS through empirical equations. The data used comes from tests conducted at the Geomechanics and Mining Equipment Laboratory, FTTM-ITB, from 2007 to 2023, and the test samples are from the Asem-Asem Basin, South Kalimantan. The probability distribution of point load index (PLI), uniaxial compressive strength (UCS), uniaxial tensile strength (UTS), and Young's modulus (E) of intact rocks is crucial for rock engineering design and construction. However, determining the type of distribution can be time-consuming. Therefore, the distribution fitting was performed using the Kolmogorov-Smirnov method. The fitting results showed that the distribution of PLI is lognormal, UCS and UTS are Weibull, and E is gamma. The correlation between UCS and E showed coefficients ranging from 111.12 to 343.26 and R-squared values from 0.53 to 0.96. The correlation between PLI and UCS had coefficients ranging from 10.96 to 21.63 and R-squared values from 0.88 to 0.98. The correlation between UTS and UCS showed coefficients ranging from 5.16 to 8.97 and R-squared values from 0.54 to 0.98. Finally, this study was compared with previous research and was found to be effective in estimating site-specific correlation coefficients and the joint probability distribution of the data.